Potash and potassium-magnesium salt of Pogojskoe rhythmic member of the western part of the northern outer side of the boarder of the Caspian depression: lithological features and formation conditions - M. V. Solomon; O. P. Goncharenko; G. A. Moscowsky (Известия высших учебных заведений: Геология и разведка)
The data has been given on the possible commercial potassium content of halogen sediments from the Pogozhskaya rhythmic member within the Western part of the North Caspian depression. It has been shown that the detailed lithological and geochemical studies, with the construction of the thickness maps, allow allocating in the section the most promising intervals with the potassium mineralization, as well as the taking into account the direction of nipping of the productive intervals and, as a consequence, choosing the priority of the sites for prospecting. Chloride type of potassium mineralization is represented by carnallites and sylvinites. The latter are the main source of the potassium ore. Sulfate salt — kainite and kieserite - are allocated only within the North-Western part of the basin. It has been found that the sylvinite layer was formed as a result of entering of the solutions with lower concentration (at the level of the halite stage) to the water basin with the strong brine of carnallite-bischofite stage . It has been revealed that the sylvite from the potash intervals of the section of the pogozhskaya rhythmic member is a product of the decomposition of carnallite.